2017
DOI: 10.1177/0883073816686910
|View full text |Cite
|
Sign up to set email alerts
|

AbobotulinumtoxinA (Dysport®) Improves Function According to Goal Attainment in Children With Dynamic Equinus Due to Cerebral Palsy

Abstract: This secondary analysis of a large (n = 241), randomized, double-blind study evaluated the efficacy of 2 doses of abobotulinumtoxinA + standard of care (SOC) versus placebo + SOC in enabling children with dynamic equinus due to cerebral palsy to achieve their functional goals using Goal Attainment Scaling. Most parents/caregivers selected goals targeting aspects of gait improvement as most relevant. Mean (95% confidence interval) Goal Attainment Scaling T scores at week 4 were higher for both abobotulinumtoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
1
13
0
2
Order By: Relevance
“…Most of the chosen goals in this study (chosen by parents in agreement with the investigators) centred on improving walking patterns, and thus the present results confirm the benefits of abobotulinumtoxinA in supporting the achievement of better gait, which is of prime importance to patients and their families. 14,17 Of note, we have also observed significant improvements versus placebo from baseline to Week 12 in the fatigue item of the Pediatric Quality of Life Inventory for both doses of abobotulinumtoxinA (10 U/kg/leg: p = .030 and 15 U/kg/leg: p = .037, the overall score was not significantly improved in either group). 23 Other studies of BoNT-A in children with CP have reported that treatment, not only reduces spasticity and improved ankle range of motion and walking pattern, but also reduces energy consumption.…”
Section: Discussionmentioning
confidence: 61%
“…Most of the chosen goals in this study (chosen by parents in agreement with the investigators) centred on improving walking patterns, and thus the present results confirm the benefits of abobotulinumtoxinA in supporting the achievement of better gait, which is of prime importance to patients and their families. 14,17 Of note, we have also observed significant improvements versus placebo from baseline to Week 12 in the fatigue item of the Pediatric Quality of Life Inventory for both doses of abobotulinumtoxinA (10 U/kg/leg: p = .030 and 15 U/kg/leg: p = .037, the overall score was not significantly improved in either group). 23 Other studies of BoNT-A in children with CP have reported that treatment, not only reduces spasticity and improved ankle range of motion and walking pattern, but also reduces energy consumption.…”
Section: Discussionmentioning
confidence: 61%
“…A collaborative goal setting environment was achieved through implementation of GAS which was found to provide a structured process that all therapists could readily follow. As described in several published papers, the setting and negotiation of SMART goals is helpful in engaging and motivating the patient because the resultant goals are worded in a way that has direct meaning to the lives of patients and their families (Bovend'Eerdt et al, 2009;Steenbeek et al, 2007;Tilton et al, 2016;Turner-Stokes, Fheodoroff, Jacinto, Maisonobe, & Zakine, 2013;Turner-Stokes, Williams, & Johnson, 2009). Our main aim was to build a comprehensive library of exercises/activities to provide a standardized therapy program that could easily be personalized to the specific needs of each patient, and tailored to their treatment goals.…”
Section: Discussionmentioning
confidence: 99%
“…It will, however, provide a standardized background of good practice against which to test the efficacy of abobotulinumtoxinA. Recent experience in a Phase-III trial of abobotulinumtoxinA for pediatric lower limb spasticity has shown the relevance of robust training and standardization of outcome measurement in providing a robust dataset that can show statistically significant and clinically relevant differences between treatment groupsboth in measures of spasticity and hypertonia and in functional measures including the GAS (Delgado et al, 2016;Tilton et al, 2016). We also believe the HETP can be implemented to improve standards of care for children with CP across countries and cultures, particularly where resources are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, the majority of TRAE were related to injection procedure and injection site pain was the most frequent. Significantly higher decreases of muscle hypertonia and spasticity (MAS, MTS), goal achievement (GAS), and overall global clinical impression (PGA) were demonstrated for the treatment groups [22,40,41]. In the double-blind phase, AboBoNT-A significantly improved observational gait scale (OGS) total scores versus placebo at week 4, and continued to improve gait throughout the OL phase [42].…”
Section: E a D I N G T O P I Cmentioning
confidence: 99%